Comparative effectiveness and persistence of TNFi and non-TNFi in juvenile idiopathic arthritis: a large paediatric rheumatology centre in the USA. (28th December 2020) - Yue, Xiaomeng; Huang, Bin; Hincapie, Ana L; Wigle, Patricia R; Li, Yuxiang; Qiu, Tingting; Lovell, Daniel J; Morgan, Esi M; Guo, Jeff J
Abstract: Objective: To evaluate the persistence and effectiveness of TNF inhibitors (TNFi) vs non-TNFi among newly diagnosed JIA patients after initiation of biologic DMARD (bDMARD). Methods: Using longitudinal patient-level data extracted from electronic medical records in a large Midwestern paediatric hospital from 2009 to 2018, we identified JIA patients initiating TNFi and non-TNFi treatment. Treatment effectiveness was assessed based on disease activity. Inverse probability of treatment weighting of propensity score was used to estimate the treatment effectiveness and Kaplan–Meier analyses were conducted to assess persistence. Results: Of 667 JIA patients, most (92.0%) were prescribed one of the class of TNFi as their initial biologic treatment. Etanercept was the most frequently prescribed (67.1%) treatment, followed by adalimumab (27.5%). Only around 5% of patients were prescribed off-label bDMARDs as their first-course treatment; however, >20% were prescribed off-label biologics as their second-course therapy. Some 7.2% of patients received four or more bDMARDs. The median persistence of the first-course bDMARD is 320 days, with TNFi being significantly longer than the non-TNFi (395 vs 320 days, P  = 0.010). The clinical Juvenile Disease Activity Score (cJADAS) reduction of TNFi users (6.6, 95% CI 5.7, 7.5) was significant greater compared with non-TNFi users (3.0, 95% CI 1.5, 4.6, P  < 0.0001) at 6-month follow-up visit. Conclusion: Persistence was significantly longer among patients initiating TNFi as their first biologic therapy than those receiving non-TNFi. Patients receiving TNF therapy had significant greater reduction of cJADAS at the 6-month follow-up visit compared with patients in the non-TNF cohort.